Equações diofantinas lineares, quadráticas e aplicações - Souza, Romario Sidrone [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Este trabalho é resultado de uma pesquisa bibliográfica sobre Diofanto e as equações que levam seu nome, as equações diofantinas. Mais especificamente, apresentamos as equações diofantinas lineares e alguns casos particulares das equações diofantinas quadráticas. Ainda, abordamos um estudo sobre alguns tópicos de teoria dos números e frações contínuas, afim de facilitar o entendimento sobre os teoremas e resultados acerca do tema central deste trabalho.

This work is the result of a bibliographical research about Diophantus and the equations that take his name, the Diophantine equations. More specifically, we present the linear diophantine equations and some particular cases of the quadratic diophantine equations. We have also studied topics about number theory and continuous fractions, in order to facilitate the understanding of theorems and results that are related to the central theme of this work.
Diophantine linear equations, quadratics and applications
Keywords: Álgebra; Diofanto; Equações diofantinas; Teoria dos números; Algebra; Diophantus; Diophantine equations; Number theory